Three Rivers Alliance - Andrews, Don, speaker; Schneider, Troy, speaker; Morgan, Ken, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The Three Rivers Alliance (TRA) was formed on July 9, 2008 as a Colorado non-profit corporation by landowners in the Republican River basin of Colorado. The goal of the organization is to preserve and strengthen the local ecosystems and the agricultural viability of their community. TRA advocates for landowners on the Republican River basin to help them gain access to resources to remove invasive species, replant vegetation, and protect wildlife on riparian and range land areas. In addition, TRA is demonstrating its ability to convene important discussions and to get people to pull together in the same direction on the same issues: to agree on problems and to seek ways to pursue constructive solutions; to find common ground; and to proceed to solve difficult issues facing the Republican River system.
Three Rivers Alliance sessions
Moderator: Ken Morgan.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Troy Schneider.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses